1996
DOI: 10.1111/j.1365-2222.1996.tb00100.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylaxis to penicillins after non‐therapeutic exposure: an immunological investigation

Abstract: these results show that non-therapeutic exposure to penicillin can cause severe symptoms and that in vitro and in vivo testing can help in the diagnosis of such cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…A recent study of IgE to chlorhexidine measured by a prototype of the ImmunoCAP in patients with positive prick test results to chlorhexidine digluconate had a lower yield of positive IgE tests, but sera were taken an average of 29 months after the reaction. 14 A decline in the IgE antibody response to chlorhexidine has previously been measured in 1 patient, 8 and the same has been described for other allergens such as penicillin 15 and insect venom. 16 In this study, serial analyses for both IgE and HR in 1 patient showed an almost identical decline over time (Fig 5, A).…”
Section: Discussionmentioning
confidence: 94%
“…A recent study of IgE to chlorhexidine measured by a prototype of the ImmunoCAP in patients with positive prick test results to chlorhexidine digluconate had a lower yield of positive IgE tests, but sera were taken an average of 29 months after the reaction. 14 A decline in the IgE antibody response to chlorhexidine has previously been measured in 1 patient, 8 and the same has been described for other allergens such as penicillin 15 and insect venom. 16 In this study, serial analyses for both IgE and HR in 1 patient showed an almost identical decline over time (Fig 5, A).…”
Section: Discussionmentioning
confidence: 94%
“…Little evidence is available in the literature concerning this problem. Resensitization studies indicate that negative patients may become positive, not only after therapeutic administration [15,16,20] but also after non-therapeutic exposure to betalactams [21].…”
Section: Discussionmentioning
confidence: 99%
“…The availability of diagnostic tests and determination of specific IgE antibodies has made it possible to study this model in great detail [1]. Clinical experience with such patients indicates that reactions can be induced by very low concentrations of drugs through the oral route, skin testing or inadvertent exposures [43][44][45]. If a subject takes amoxicillin or another BL derivative and develops an anaphylactic response after an interval of over 1 h, we are likely dealing with an accelerated reaction for which the proposed mechanism is a T cell response [46•].…”
Section: Underlying Mechanismsmentioning
confidence: 99%